The prospectively-reported implementation update and score (PRIUS): a new method for capturing implementation-related developments over time - Edward J. Miech; Nicholas A. Rattray; Dawn M. Bravata; Barbara J. Homoya; Jennifer Myers; Teresa M. Damush (BMC, 2019)
Abstract Background Implementation of new programs within healthcare systems can be extraordinarily complex. Individuals within the same healthcare organization often have different perspectives on how implementation of a new program unfolds over time, and it is not always clear in the midst of implementation what issues are most important or how to address them. An implementation support team within the Veterans Health Administration (VHA) sought to develop an efficient method for eliciting an ongoing, detailed and nuanced account of implementation progress from multiple viewpoints that could support and inform active implementation of two new VHA programs. Methods The new Prospectively-Reported Implementation Update and Score ("PRIUS") provided a quick, structured, prospective and open-ended method for individuals to report on implementation progress. PRIUS updates were submitted approximately twice a month. Responding to the prompt "What are some things that happened over the past two weeks that seem relevant from your perspective to the implementation of this project?", individuals scored each update with a number ranging from + 3 to − 3. Results In 2016-17, individuals submitted over 600 PRIUS updates across the two QI projects. PRIUS-based findings included that staff from different services reported fundamentally different perspectives on program implementation. Rapid analysis and reporting of the PRIUS data led directly to changes in implementation. Conclusions The PRIUS provided an efficient, structured method for developing a granular and context-sensitive account of implementation progress. The approach appears to be highly adaptable to a wide range of settings and interventions.